A casebook of ethical challenges in neuropsychology - Bush, Shane S., 1965- (London ; New York : Taylor & Francis, 2005)
The American Psychological Association published a revision of the Ethical Principles of Psychologists and Code of Conduct in 2002. This text, a companion to the 2002 text Ethical Issues in Clinical Neuropsychology by Bush and Drexler, presents the reader with common ethical challenges in neuropsychology. This text examines the differences between the 1992 and 2002 APA Ethics Codes as they relate to neuropsychological activities. The authors present cases and discuss ethical issues related to neuropsychological practice with a variety of patient populations and in a variety of clini.
Section 1. Differences between the 1992 and 2002 APA ethics codes : a brief overview / Shane S. Bush -- section 2. Ethical challenges in forensic neuropsychology -- section 3. Ethical challenges in neuropsychology in medical settings -- section 4. Ethical challenges in neuropsychology in psychiatric settings -- section 5. Ethical challenges in neuropsychology in rehabilitation settings -- section 6. Ethical challenges in the neuropsychology of pain -- section 7. Ethical challenges in pediatric neuropsychology -- section 8. Ethical challenges in geriatric neuropsychology -- section 9. Ethical challenges with ethnically and culturally diverse populations in neuropsychology -- section 10. Ethical challenges with the use of information technology and telecommunications in neuropsychology -- section 11. Ethical challenges in neuropsychological research -- section 12. Ethical challenges in neuropsychological test development -- section 13. Ethical challenges in the determination of response validity in neuropsychology.
Includes bibliographical references and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Neuropsychology -- Philosophy; Neuropsychology -- Moral and ethical aspects; Neuropsychology -- Case studies; Neuropsychology -- ethics; Ethics, Clinical; MEDICAL -- Ethics; Neuropsychology; Neuropsychology -- Philosophy; Neuropsychologie; Ethiek; Electronic books; Case studies